The Application of Augmentative Alternative Communication (AAC) Through Picture Exchange Communication System (PECS) Media to Improve Communication Skills of Children With Autism: The Application of Augmentative Alternative Communication (AAC) Through Picture Exchange Communication System (PECS) Media to Improve Communication Skills of Children With Autism - Lutfianti, Zerlinda; Ataqi, Andre Eprilia; Asmiati, Neti; Putri, Elisa; Puspitasari, Reva; Widya, Laluna Anjelini; Hikmatullah, Hikmatullah; Saputra, Nedi; Sukmariah, Sukmariah; Handayani, Anisa; Jazilatusyifa, Jazilatusyifa (PT Ilmu Inovasi Nusantara, 2023)
The subjects in this research were autistic individuals. Based on observations, it is known that individuals experience problems in non-verbal communication that result in individuals being unable to convey or communicate an activity they want to others. The purpose of this research is to determine the improvement of communication skills of autistic children by applying Augmentative Alternative Communication (AAC) through Picture Exchange Communication System (PECS) media. The research method used is experimental research with the type of Single Subject Research (SSR) research with the design A1-B-A2. Data collection techniques in this study used tests, while the target behavior in this study was 1) able to show pictures of daily activities. The results showed that the application of Augmentative Alternative Communication (AAC) through Picture Exchange Communication System (PECS) media can improve the communication skills of autistic children. The increase is indicated by the mean level value that increases in each phase through percentage measurement. Baseline phase 1 (A1) obtained a mean level of 28%, intervention phase (B) obtained a mean level of 47%, and baseline phase 2 (A2) obtained a mean level of 46%. From the acquisition of the mean level, it can be seen that the mean level shown in baseline 1 with baseline 2 has increased significantly. This shows that the application of Augmentative Alternative Communication (AAC) through Picture Exchange Communication System (PECS) media can improve the communication skills of autistic children